A new perspective on macrophage-targeted drug research: the potential of KDELR2 in bladder cancer immunotherapy - Zhao, Zhiyi; Jia, Hongling; Sun, Zhou; Li, Yumeng; Liu, Lingyun (Frontiers in Immunology, 2024)
IntroductionBladder cancer was recognized as one of the most common malignant tumors in the urinary system, and treatment options remained largely limited to conventional surgery, radiotherapy, and chemotherapy, which limited patient benefits.MethodsResearchers constructed an RNA transcriptome map of bladder cancer by integrating single-cell RNA sequencing and clinical data, identifying potential molecular targets for diagnosis and treatment. We also verified the antitumor activity of the target through in vitro experiment.ResultsA distinct tumor cell subpopulation characterized by elevated S100A8 expression exhibited high copy number variation, high stemness, and low differentiation. It interacted with myeloid cells via the MIF-(CD74+CD44) and MIF-(CD74+CXCR4) signaling pathways. This study underscored KDELR2’s role in promoting cell proliferation, invasion, and migration, providing new therapeutic insights. Prognostic analysis revealed that KDELR2 correlated with poor survival, higher immune scores, and increased macrophage infiltration.DiscussionThe findings suggested that patients with high KDELR2 expression might benefit from immune checkpoint therapy. KDELR2 was also shown to enhance bladder cancer cell proliferation, invasion, and migration, highlighting it as a promising target for macrophage-focused drug development.